“Helt Texas, Morgan Kane!”: Notes on the Pedagogies of Finding, Documenting, and Teaching the American West in Norwegian Backyards - Stefan Rabitsch (American Studies in Scandinavia)
Applying transnational/global Wests methodologies, this article is predicated on an admittedly polemic claim: the American West can be found on many (if not all) foreign shores. This article showcases the pedagogies employed in teaching graduate-level cultural studies seminars on the American West in a Norwegian context. American studies students were tasked with locating and retrieving traces/echoes/spores of the American West in their proverbial backyards. They conducted cultural geography fieldwork with a view to generating generation-specific content in the form of short video reels. The resultant documentary archive gestures at rather clear patterns. For example, the students’ findings included but were not limited to country-specific (re)imaginings of the mythic West in different media, heterotopic spaces of performance, play, consumption and the hyperreal, instances of ‘playing Indian,’ iconographic scatterings, cowboy/Western poetics in music, and more. Ultimately, this article illustrates how that which we study from afar may be found in more local(ized) Norwegian contexts, imaginaries, and cultural practices.